979 ARRHYTHMOGENIC CARDIOMYOPATHY: LONG-TERM FOLLOW-UP OF A PROSPECTIVE MULTICENTRE COHORT. (15th December 2022) - De Lio, Francesca; Toso, Elisabetta; Bocchino, Pier Paolo; Blandino, Alessandro; Fioravanti, Francesco; Gallo, Cristina; Garberoglio, Lucia; Richiardi, Elena; De Ferrari, Gaetano Maria; Gaita, Fiorenzo
Abstract: Background: Arrhythmogenic cardiomyopathy (ACM) is an inherited heart muscle disease characterized by fibro-fatty replacement of predominantly right, left or biventricular myocardium. The clinical course of ACM is characterized by high risk of abrupt arrhythmic ventricular events, potentially leading to sudden cardiac death (SCD), and by progressive impairment of biventricular systolic function, which may lead to heart failure (HF)-related death, with an estimated overall yearly mortality ranging from 0.08% to 3.6% among studies. Aim: This study sought to assess the long-term follow-up of a cohort of ACM patients from the Piedmont region of Italy, specifically evaluating the cumulative incidence of SCD, HF-related death and heart transplantat. Methods: Patients who received a definite ACM diagnosis according to the latest available International Task Force Criteria (ITFC) at three different institutions in Piedmont ("Cardinal Massaia" Hospital of Asti, "Azienda Ospedaliera Ordine Mauriziano" of Turin and "Città della Salute e della Scienza" Hospital of Turin) between 1982 and March 2022 were prospectively enrolled. Clinical, electrocardiographic and imaging data were collected at baseline and during follow-up. The occurrence of two coprimary composite endpoints was evaluated, namely the arrhythmic composite endpoint of SCD or aborted SCD and the HF-related composite endpoint, including heart transplant for end-stage HF or cardiac death due to pump failure. Independent predictors of the coprimary composite endpoints were also assessed by means of multivariable analysis. Results: The overall population included 97 patients; mean age at diagnosis was 38.2 ± 14.3 years; 66 (68%) patients were male. Median follow-up was 12.9 years (interquartile range 0-38 years). The composite arrhythmic outcome occurred in 10 (10.3%) patients and the composite HF outcome occurred in 13 (13.5%) patients. Overall, 19 (19.6%) patients died: seven (37%) patients died from SCD, four (21%) patients died of end-stage HF and eight (42%) patients died from non-cardiac causes. The cumulative incidence of cardiac death was 1.65% per year. Aborted SCD occurred in 3 (3%) patients, sustained ventricular tachycardias in 51 (52%), HF in 17 (18%) and atrial fibrillation in 21 (22%); forty-seven (48%) underwent an implantable cardioverter defibrillator implantation (ICD) and 8 (8%) patients underwent heart transplant. Mean interval between ACM diagnosis and heart transplant was 130.4 ± 75.3 months. At univariable analysis, the presence at baseline of terminal activation duration (TAD) ≥ 55 ms on surface electrocardiogram (p value 0.037), right atrium dilatation at transthoracic echocardiography (p value 0.021) and cardiac magnetic resonance imaging (p value 0.031) and palpitations as main clinical presentation (p value 0.017) were associated with the occurrence of the arrhythmic endpoint. At multivariable analysis, baseline TAD ≥ 55 msec was the only predictor of the composite arrhythmic endpoint (odds ratio 12.5, 95% confidence interval 1.29 to 121.26, p value 0.029). At univariable analysis, the presence of epsilon waves (p value 0.017), TAD ≥ 55 ms (p value 0.020) and T wave inversion in leads V1-V3 (p value 0.022) on surface electrocardiogram, HF (p value 0.018) or atrial arrhythmias (p value < 0.001) at presentation and New York Heart Association (NYHA) class III to IV at diagnosis (p value 0.002) were significantly associated with the composite HF-related endpoint. At multivariable analysis, the presence of atrial arrhythmias at presentation was the only predictor of the HF-related composite endpoint (odds ratio 10.8, 95% confidence interval 1.29 to 90.32, p value 0.028). Conclusions: In this multicenter cohort of 97 ACM patients, the cumulative incidence of cardiac death was 1.65% per year at long-term follow-up. Arrhythmic death accounted for the majority of cardiac fatal events (64%), confirming the peculiar predisposition to SCD of ACM patients. Evolution towards end-stage HF and cardiac death due to pump failure were common.